Literature Review of Studies about Violence at School and Recommendations for Teachers - Karakuş Gülçin (Sciendo, 2022)
Introduction: Violence is a very complex and particular concept and it is difficult to make a precise definition, since acceptable and unacceptable behaviour patterns for each society vary according to social norms, time and value judgments of what harms that society. School violence results in students' loss of concentration, poor academic success, bunking of courses, and depression. Violence is a global problem, solution depends on an integrated approach in which educators, parents and learners work together. Considering negative consequences of violence, reduction or even prevention of violence at school will not only increase quality of education and training, but also support education process to become more productive. The aim of this review is to examine studies on school violence in literature, to determine causes of violence at school and present suggestions for solutions. This type of study may also have the potential to shed light on future work on violence in schools. For this reason, the purpose of this study is to examine the studies on violence at school and to present a review on violence prevention.